2021
DOI: 10.1080/23766808.2021.1953893
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory and leaf traits of two tree species from different successional stages in a tropical dry forest

Abstract: Leaf traits are analyzed as essential drivers for the evolutionary and ecological role of plant defense mechanisms. Plants show leaf trait variation as a response to the diverse environmental conditions, like different successional stages. Those variations can impact leaf herbivory rates and drive changes in the allocation of plant resources. In this study, we aimed at comparing the expression of leaf defenses in established plants over different successional stages in a tropical dry forest to understand how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Letters above bars indicate significant differences between strata. Mauffette 2002; Kause et al 1999) did not promote insect herbivory, while leaf traits thought to be unfavourable (i.e., higher leaf carbon content and leaf tannin content) (de Sena et al 2021;Stiegel et al 2017) did not inhibit insect herbivory. Horizontally, no significant correlation was found between insect herbivory and leaf traits (Figures 2 & 3).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Letters above bars indicate significant differences between strata. Mauffette 2002; Kause et al 1999) did not promote insect herbivory, while leaf traits thought to be unfavourable (i.e., higher leaf carbon content and leaf tannin content) (de Sena et al 2021;Stiegel et al 2017) did not inhibit insect herbivory. Horizontally, no significant correlation was found between insect herbivory and leaf traits (Figures 2 & 3).…”
Section: Discussionmentioning
confidence: 84%
“…Higher leaf nitrogen content promoted leaf consumption in sugar maple (Acer saccharum) (Fortin & Mauffette 2002) and Handroanthus ochraceus (Bignoniaceae) (Silva et al 2012). de Sena et al (2021) found that the high content of leaf phenolic compounds of Aspidosperma pyrifolium and Cenostigma pyramidale can negatively influence insect herbivory.…”
Section: Introductionmentioning
confidence: 99%